Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1002/bip.21523
|View full text |Cite
|
Sign up to set email alerts
|

Conformation dependence of the CαDα stretch mode in peptides: Side‐chain influence in dipeptide structures

Abstract: We have shown by theoretical studies of alanine peptides that the C(α)D(α) stretch frequency could be particularly useful for determining peptide structure because of its sensitivity to the ϕ,ψ torsion angles at the C(α) atom. To demonstrate that this is a robust methodology worthy of experimental exploration, we have also shown that this mode is even more determinative of conformation in aqueous solution, mainly as a result of the development of differential C(α)--D(α)···O(water) interactions. As further assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…These insights make it clear that such a relative stability is likely to be sensi-tive to such factors as the length and the sequence of peptide conformations, as well as on the nature of the side chains. 50,91 We are currently investigating the influences of these factors on the energetics. The generally observed temperature dependence of the circular dichroism spectra of peptide systems indicates that the entropic component of the free energy difference will favor the b-conformation as the temperature increases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These insights make it clear that such a relative stability is likely to be sensi-tive to such factors as the length and the sequence of peptide conformations, as well as on the nature of the side chains. 50,91 We are currently investigating the influences of these factors on the energetics. The generally observed temperature dependence of the circular dichroism spectra of peptide systems indicates that the entropic component of the free energy difference will favor the b-conformation as the temperature increases.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the relative intensity of the two characteristic bands in the CD spectrum, which according to theory is a function of the number of adjacent PPII conformations, 19 may help in clarifying this issue. We have proposed a new technique that could provide this information through an analysis of the C a D a stretch mode at individually isotopically substituted sites, [47][48][49][50] this frequency being found to depend mainly on the u,w torsion angles at the site. We hope that this methodology can be implemented in studies of such systems.…”
Section: Introduction Wmentioning
confidence: 99%
“…Therefore, these five bands only correspond to the five conformers of 1-propanol. In previous studies, the results from theoretical predictions have shown that the C–H stretching vibrations can be used to characterize the backbone conformations of protein and peptides [ 9 , 10 , 11 , 12 ]. However, the experimental evidence is limited.…”
Section: C–h Stretching Vibration As a Conformational Probementioning
confidence: 99%
“…Therefore, one of the important aspects of applying vibrational spectroscopy is to develop the appropriate vibrational probes that can characterize molecular specific information such as the conformation and intermolecular interaction. Many chemical groups have been established as vibrational probes in the literature, including the thiocyanate group (–SCN), azide group (–N 3 ), diazo group (–N 2 ), the alkyne (–C≡C–), amide group (–CONH 2 ), amine group (–NH 2 ), carbonyl group (–C=O), hydroxyl group (–OH), –SH group, –CH group, and so on, as summarized in recent several reviews [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. For example, using the site-specific nitrile group (–C≡N) as a probe of protein structure, it was shown that –CN frequencies could discriminate between the solvent-exposed residues and residues buried in the hydrophobic core of a protein [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation